The Effectiveness of Role-Play and Task-Based-Strategy to Teach Speaking to Students with Different Learning Styles - Nugroho Dimastoro; Dwi Anggani Linggar Bharati (Universitas Negeri Semarang, 2022)
Many students feel difficult to study English, especially in speaking skills because the teaching process cannot stimulate students' interest. Less interaction in the teaching process forces the teachers to adjust to this condition by implementing a creative strategy to improve the student’s motivation and achievement. Using an appropriate strategy will help to solve the problem. This study aims to explain whether Role-play and Task-Based Language Teaching (TBLT) is effective to teach speaking to students with different learning styles. The learning styles we use are auditory and visual. This study used a 2x2 factorial design in the experimental study. It was used to collect the data from 60 students divided into two groups; they were experimental group 1 and experimental group 2. They were treated with different strategies: Role-play and TBLT. The type of data analysis in this experimental study is quantitative analysis to analyze speaking tests, questionnaires, and observation sheets. In this study, the researchers employ two analysis techniques to analyze the data. The techniques of data analysis used descriptive and inferential statistics. The result shows a significant difference between Role-play and TBLT strategies to teach speaking to students with different learning styles. The Role-play was more effective than the TBLT strategy to teach speaking to auditory and visual learning styles. Based on the analysis, there was no interaction among the strategies, learning styles, and speaking skills. The researchers also briefly recommend the use of Role-play and TBLT to be applied in various ways and at different levels.